STATIS methodology: an overview - Grilo, Luís M.; Oliveira, Manuela; Garção, Eugénio; Mexia, João T. (My University, 2022)
The STATIS (Structuration des Tableaux a Trois Indices de la Statistique) methodology is a data analysis technique which computes Euclidean distances between studies of the same observations obtained in k different circumstances. The Escoufier operators are used to obtain a geometrical representation for the studies in a series. In this study we present developments in the STATIS methodology, namely how to make inferences when for each treatment of a model we have a series of studies